Human Resources (HR) In Education Management - Bahdin Nur Tanjung (BIRCU, 2020)
Human resources (HR) has a significant role in every activity in an institution including educational institutions. Human resources (HR) must be able to be managed or managed properly in accordance with their functions so that these human resources (HR) can play a role in accordance with their duties and functions in the institution they are in. Human resource management is a very important aspect in the education process in general. Therefore functions in the management of human resources must be carried out optimally so that the needs relating to the goals of individuals, organizations / institutions, organizations or institutions can be achieved. Besides that, with good human resource management procedures, it is expected that the shortcomings and problems faced by the Indonesian nation, which are related to competitiveness, can be overcome.